Answer:
y = 3x + 2
Step-by-step explanation:
The equation for two points on a line is generated from the straight line equation y = mx + b ---------------- eqn (i)
where m, the slope = (y2 - y1) / (x2 - x1)
therefore for (0,2) and (1,5) m = (5 - 2)/(1 - 0) = 3
This implies that eqn (i) can be rewritten as:
y = 3x + b ------------------- eqn (ii)
pickintg the point (0,2) and substituting into eqn (ii)
2 = 3(0) + b
this implies that b = 2
for confirmation with (1,5)
5 = 3(1) + b
b = 5 - 3 = 2
hence m = 3, b = 2
the equation is y = 3x + 2